2014
DOI: 10.1016/j.cell.2014.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Hexosamine Pathway Metabolites Enhance Protein Quality Control and Prolong Life

Abstract: Aging entails a progressive decline in protein homeostasis, which often leads to age-related diseases. The endoplasmic reticulum (ER) is the site of protein synthesis and maturation for secreted and membrane proteins. Correct folding of ER proteins requires covalent attachment of N-linked glycan oligosaccharides. Here, we report that increased synthesis of N-glycan precursors in the hexosamine pathway improves ER protein homeostasis and extends lifespan in C. elegans. Addition of the N-glycan precursor N-acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
212
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(224 citation statements)
references
References 50 publications
11
212
1
Order By: Relevance
“…It has also been reported that increased HBP flux by gainof-function mutation of GFAT1 or exogenous addition of GlcNAc controls protein quality control through increased autophagy, ER-associated degradation, and proteasome activ- ity, thereby exerting cytoprotective effects in Caenorhabditis elegans disease models and extending lifespan (Fig. 3B) (66). Furthermore, we and others have recently shown that O-GlcNAc on proteins such as tau, TAK1-binding protein, ␣-synuclein, and PFK1 inhibits oligomerization or aggregation in the context of disease states (36,67,68).…”
Section: O-glcnac and Cancer Cell Survivalmentioning
confidence: 99%
“…It has also been reported that increased HBP flux by gainof-function mutation of GFAT1 or exogenous addition of GlcNAc controls protein quality control through increased autophagy, ER-associated degradation, and proteasome activ- ity, thereby exerting cytoprotective effects in Caenorhabditis elegans disease models and extending lifespan (Fig. 3B) (66). Furthermore, we and others have recently shown that O-GlcNAc on proteins such as tau, TAK1-binding protein, ␣-synuclein, and PFK1 inhibits oligomerization or aggregation in the context of disease states (36,67,68).…”
Section: O-glcnac and Cancer Cell Survivalmentioning
confidence: 99%
“…Moreover, this result emphasizes that compartmentalization of stressresponse pathways does not preclude extensive cross-talk between sensors and that this communication may make it difficult at times to determine the actual location of the proteotoxic species (Liu and Chang 2008;Buchberger et al 2010;Richter et al 2010;Heldens et al 2011;Roth et al 2014). There are two other studies that make experimental inferences based on the notion that SRP-2 H302R ::YFP was aggregating within the ER instead of the cytosol (Denzel et al 2014;Hou et al 2014). First, Hou et al (2014) show that loss-of-function of the Mediator subunit, mdt-15, causes an increase in ER membrane phospholipid saturation and activation of the UPR.…”
Section: Discussionmentioning
confidence: 99%
“…While these animals expressing mutant SRP-2 could be used to study the effects of cytosolic serpin polymerization, the markedly different expression patterns, inhibitory profiles, and subcellular localization of SRP-2 compared to those of human NS/ SERPINI1 confound the ability to use these animals to model accurately the interaction between aging and ER overload in patients with the serpinopathy, FENIB. Furthermore, interesting experimental results regarding the effects of mutant SRP-2 on ER proteostasis pathways should be viewed from the perspective that this proteotoxic stress originated from within the cytosol and not the ER (Denzel et al 2014;Hou et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] As the body ages, damaged organelles and abnormal proteins accumulate, disrupting cellular homeostasis. [9][10][11] A system for eliminating damaged organelles, proteins, and intracellular pathogens is critical for maintaining cellular homeostasis as the body ages. In recent years, it has become evident that autophagy plays a pivotal role in this regard.…”
Section: )mentioning
confidence: 99%